DNA methylation of membrane-bound catechol-O-methyltransferase in Malaysian schizophrenia patients - Abd Rahim, Nour El Huda; Ku Zaifah, Norsidah; Mohd Rahim, Nabil Fikri; Mohd Noor, Hanisah; Abdullah, Kartini; A.Talib, Norlelawati (Blackwell Publishing, 2018)
AIM: